Marxian Socio-Political Economic Theory: Two Schools of Thought: Part-II - Sehgal, M. L. (Advances in Social Sciences Research Journal, 2020)
Marx, an idealist, who believed ‘Capitalism to be an Evil’ and ‘Socialism a Harbinger of Prosperity’, propagated his economic ideas whose basic Pillar was the Labor Theory of Value (LTV) which included Surplus –Value (SV), Falling Tendency of Rate of Profit, Price of a Commodity, Supply and Demand’ Relation, Inflation and Interest Rates. His Socio-political thought included the state would be the Monopolist without anybody owning any private property with religion being the opiate of the masses. He preached class struggle but ignored the middle class. He wanted to do away the State even with the violent Revolution. All this brought him in conflict both with his contemporary economists as well as with the future generation of economists. The 150 old Socio-political Economic Theory of Marx, though a noble idea, could not stand the test of the times and started falling under its weight. The duality in the minds of the people about its utility and applicability is best described by the celebrated Physicist- Einstein’s viewpoint which speaks volumes of the aura of the man named Karl Heinrich Marx: “I am convinced (that) there is only one way to eliminate these grave evils, namely through the establishment of a socialist economy, accompanied by an educational system which would be oriented toward social goals. In such an economy, the means of production are owned by society itself and are utilized in a planned fashion. A ‘planned economy’, which adjusts production to the needs of the community, would distribute the work to be done among all those able to work and would guarantee a livelihood to every man, woman, and child” But look at the lurking fear in the mind of the genius about the ‘planned economy’ as: “Nevertheless, it is necessary to remember that a planned economy is not yet socialism. A planned economy as such may be accompanied by the ‘complete enslavement of the individual’. The achievement of socialism requires the solution of some extremely difficult socio-political problems: how is it possible, because of the far-reaching ‘centralization of political and economic power’, to ‘prevent bureaucracy from becoming all-powerful and overweening’? How can the ‘rights of the individual be protected’ and therewith a ‘democratic counterweight to the power of bureaucracy be assured’?”